Association of Staphylococcus nasal colonization and HIV in end-stage renal failure patients undergoing peritoneal dialysis - Ndlovu, Kwazi C. Z. (Ren Fail, 2019)
Introduction: Staphylococcal infections can cause significant morbidity in patients undergoing dialysis. This study evaluated the effects of HIV infection on nasal carriage of Staphylococcus aureus, staphylococcal peritonitis, and catheter infection rates in patients with end-stage renal failure managed with continuous ambulatory peritoneal dialysis (CAPD). Methods: Sixty HIV-positive and 59 HIV-negative CAPD patients were enrolled and followed up for up to 18 months. S. aureus nasal carriage (detected by nasal swab culture), Staphylococcal peritonitis (diagnosed by clinical presentation, and CAPD effluent Staphylococcal culture and white blood cell count ≥100 cells/µL), and catheter infections (including exit site and tunnel infections) were assessed monthly. Results: At 18 months, S. aureus nasal carriage rates were 43.3% and 30.5% (p = 0.147) and the methicillin-resistant S. aureus (MRSA) nasal carriage rates were 31.7% and 13.6% (p = 0.018) for the HIV-positive and HIV-negative cohorts, respectively. The HIV-positive cohort was associated with increased hazards for staphylococcal peritonitis, (adjusted hazard ratio [AHR] 2.85, 95% confidence interval [CI] 1.19–6.84, p = 0.019) due to increased coagulase-negative staphylococcal (CNS) peritonitis rate in the HIV-positive cohort compared with the HIV-negative cohort (0.435 vs. 0.089 episodes/person-years; AHR 7.64, CI 2.18–26.82, p = 0.001). On multivariable analysis, CD4+ cell count <200 cells/µL, diabetes, and S. aureus nasal carriage were found to be independent predictors of S. aureus peritonitis. Conclusions: These findings suggest that HIV infection may be a risk factor for MRSA nasal colonization and may increase the risks of CNS peritonitis, while a CD4+ cell count <200 cells/µL and S. aureus nasal carriage may be important predictors of S. aureus peritonitis.